PENGARUH IMPLEMENTASI PROGRAM SUSTAINABLE FINANCE TERHADAP OPERATING EFFICIENCY RATIO BANK TAHUN 2017-2022 - Julian Felix Armando; Setyo Tri Wahyudi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research is aimed for examining the impact of the implementation of sustainable finance program policies that projected by the sustainability report, Ethernet Channel, and Green Credit which are examine for it’s influene on the Operational Efficiency Ratio of banks that listed on the IDX that projected by BOPO in 2017-2022. Through the results of research on 6 banks that are observed by purposive sampling, it shows that ethernet channel product with digital innovation encourage customer efficiency which supports bank operational efficiency. Contrary to the Sustainability Report and Green Credit which actually creates additional costs and risks as well as the characteristics of each program that encourages inefficiency in the observed banks.